Analysis of Tax Court Appeal Verdict for Corporate Income Tax: Indonesian Case - Ahmad Deza PERDANA; Siti NURYANAH (Communications of International Proceedings, 2020)
There are a huge percentage of Indonesia tax court appeal decisions that were won by taxpayers. This study aims to determine from the tax court appeal decision about the characteristics of taxpayers who file an appeal of their dispute with Directorate General of Tax to the Tax Court, the causes of the dispute, the methods and techniques used for auditing corporate income tax on the dispute, and how the relationship between these factors and the verdict of the tax court appeal decision especially in corporate income tax dispute. This research was conducted using content analysis and binomial logistic regression.. The results of the logistic regression test found two variables that had a significant direct effect on the outcome of the verdict, two of them are cause of the dispute due to legislation or regulations and the annulment of dispute plead due to the tax audit method used.
Keywords: Tax compliance; principles of tax; tax dispute; tax court; appeal.